Design of an mHealth technology for cardiovascular risk stratification scores supported by Health Literacy - Galeno, Daniele Souto (2020)
The objective was to develop a low and high fidelity design prototype in the light of Health Literacy and to contribute with the health professional to the choice of the most appropriate cardiovascular risk score for each individual. Methodological study using the methodology of the participatory interaction design process centered on the user, with contributions from an interdisciplinary team composed of nutritionist, nurse and designer. Contributes to the design conception of ten low fidelity screens and ten high fidelity screens, based on the checklist, with recommendations for the construction of health technologies, considering fundamental aspects of Health Literacy. We sought, in the low and high fidelity prototypes, to develop an interactive and pleasant layout to facilitate the use by health professionals.